Given the word problem, we can deduce the following information:
1.
![\begin{gathered} f(x)=x^3-10 \\ g(x)=f(x)+14 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5gjgly2bbdsb3fft428ud0kvo60xljp7yx.png)
To fully understand the given given functions, we graph each functions first.
The graphs are shown below:
We plug in f(x)=x^3 -10 into g(x)=f(x)+14. So,
![\begin{gathered} g(x)=f(x)+14 \\ =x^3-10+14 \\ \text{Simplify} \\ g(x)=x^3+4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q4dnz2n479ioy7xy4qhqh29jskofuomykj.png)
Therefore, the answer is C.
into g(x)=